2021
DOI: 10.1016/j.ebiom.2021.103737
|View full text |Cite
|
Sign up to set email alerts
|

Electrical stimulation alters muscle morphological properties in denervated upper limb muscles

Abstract: Background Damage to lower motor neuron causes denervation and degeneration of the muscles affected. Experimental and clinical studies of muscle denervation in lower extremities demonstrated that direct electrical stimulation (ES) of muscle can prevent denervation atrophy and restore contractility. The aim of this study was to identify possible myogenic effect of ES on denervated forearm and hand muscles in persons with spinal cord injury (SCI) and tetraplegia. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…Furthermore, several studies have confirmed that the recovery of skeletal muscle innervation is beneficial for the muscles to recruit neurotrophin and achieve regeneration 34–36 . Subsequently, the muscle fibers also secreted myogenic trophic factors to influence the survival and function of motoneurons in a retrograde manner 37 . In addition, some studies have reported that electrical stimulation of the skeletal muscle in situ can prevent atrophy; this might be because of improvements of muscle circulation and metabolism 24,30,38 .…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, several studies have confirmed that the recovery of skeletal muscle innervation is beneficial for the muscles to recruit neurotrophin and achieve regeneration 34–36 . Subsequently, the muscle fibers also secreted myogenic trophic factors to influence the survival and function of motoneurons in a retrograde manner 37 . In addition, some studies have reported that electrical stimulation of the skeletal muscle in situ can prevent atrophy; this might be because of improvements of muscle circulation and metabolism 24,30,38 .…”
Section: Discussionmentioning
confidence: 98%
“…Each 10-minute procedure consisted of two parts: the first part (5 minutes) -short-wave laser stimulation of peripheral segments, the second part (20 minutes) -short-wave LT of the nerve trunk proximal to the level of damage. For shortwave LT [8] sciatic nerve, the SN trunk in the middle third of the thigh was irradiated. The procedures were performed every other day (Monday, Wednesday, Friday).…”
Section: Methodsmentioning
confidence: 99%
“…Denervation atrophy results in a decrease in muscle fiber diameter and a partial to complete transformation of muscle tissue into connective and adipose tissue ( 35 ). In a previous study, we demonstrated that in early as well as chronic damage to the LMN, electrostimulation with long pulses enabled maintenance and restoration of muscle properties ( 20 ). In accordance with our results and with the research carried out on the muscles of the lower limb ( 36 ), an early start of this type of stimulation is recommended.…”
Section: Introductionmentioning
confidence: 97%
“…Since ES with long and short pulses has been recognized as a treatment method in rehabilitation, there is scientific evidence of its effectiveness (10). Afferent and efferent stimulation for neuromodulation (11,12), motor learning, and/or relearning of functions (13)(14)(15), strengthening of individual muscles or muscle groups (16,17), contracture prophylaxis and maintenance or improvement of muscle properties (18)(19)(20) are essential for the treatment of the upper limb in tetraplegia.…”
Section: Introductionmentioning
confidence: 99%